Frequency of risk factors for chronic noncommunicable diseases among physicians in Russian Federation on the model of Tomsk Region - O. S. Kobyakova; E. S. Kulikov; I. A. Deev; A. A. Almikeyeva; I. D. Pimenov; E. A. Starovoitova (Кардиоваскулярная терапия и профилактика)
Aim. To determine the frequency and structure of risk factors (RF) for chronic noncommunicable diseases (CNCDs) among physicians in the Tomsk Region.Material and methods. The questionnaire was compiled based on the methodological guidelines “Monitoring of risk factors for chronic noncommunicable diseases in practical healthcare”. The questionnaire was provided in electronic format and posted on the site http://www. golosaonline.ru/medto.Results. Doctors of the Tomsk region revealed a high frequency of such RF for CNCDs as chronic as hypodynamia (45,7%), improper feeding (67,6%) and overweight (34,7%).Conclusion. The study showed that the frequency of RF for CNCDs in a Tomsk region was lower than the same one in general population. However, there is a need to develop practical guidelines for healthcare workers.